Photophysiological Mechanism of Dense Planting to Increase the Grain Yield of Intercropped Maize with Nitrogen-Reduction Application in Arid Conditions - Hong Fan; Wen Yin; Cai Zhao; Aizhong Yu; Zhilong Fan; Falong Hu; Jindan Zhang; Qiang Chai (Agronomy, 2022)
Leaf photophysiological characteristics are the main indexes that determine crop yield formation. However, it remains unclear whether photosynthesis is systematically regulated via the cropping pattern and nitrogen supply when maize crops are planted with a high density. So, a field experiment that had a three-factor split-plot arrangement of treatments was conducted from 2020 to 2021. The main plot was two cropping patterns that included the sole cropping of maize and wheat–maize intercropping. The split plot had two nitrogen application rates: a traditional nitrogen application rate (N2, 360 kg ha−1) and one reduced by 25% (N1, 270 kg ha−1) for maize. The split–split plot had three planting densities: a traditional density (M1, 78,000 plant ha−1), a medium density (M2, 10,400 plant ha−1), and a high density (M3, 129,000 plant ha−1) for sole maize; the corresponding densities of intercropped maize were 45,000, 60,000, and 75,000 plant ha−1, respectively. The grain yield, the photosynthetic traits, and chlorophyll a fluorescence of the maize were assessed. The results showed that a 25% nitrogen reduction and dense planting had a negative impact on the individual maize’s photosynthesis. However, intercropping could alleviate these drawbacks. When the maize was grown in the intercropping system at a lower nitrogen level and a medium planting density (IN1M2), the photosynthetic traits were better or similar to those of the traditional treatment (SN2M1) at the reproductive growth stage. Moreover, IN1M2 improved the light energy distribution among photochemistry, photo-protective and heat dissipation process of maize compared with SN2M1. A grey relation analysis demonstrated that the Pn and Tr of the individual maize played the most significant role in the group’s productivity. Thus, the IN1M2 treatment achieved the highest grain yield and can be recommended as a feasible agronomic practice in oasis-irrigated regions.